Analysis of Foreign Public and Private Debt on Economic Growth in Indonesia - Papilaya, Maria (Efficient: Indonesian Journal of Development Economics, 2024)
This study investigates the role of foreign debt in Indonesia's economic growth by examining both public and private sector contributions. utilizing data from recent reports and empirical analyses, the study employs granger causality tests and ardl modeling techniques to explore the relationships between public sector debt, private sector debt, and economic growth. findings suggest that while public sector debt exhibits a significant negative relationship with economic growth in both short and long terms, private sector foreign debt positively influences long-term economic growth. these results underscore the importance of foreign debt instruments in bridging financing gaps and stimulating economic development in Indonesia.